Process Approach as Skill Enhancer in Writing Recount Text: A Literature Research - Ali Mustofa; Ahmad Syafi'i (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2020)
The process writing approach treats writing as a process rather than a completed product. Writing studies are conducted as part of the process due to the completion of the written text. In writing classes, this approach tends to focus on the student, and the teacher only acts as a guide. The process writing approach includes actions that occur when a written text is created. This research analyzed the benefits of the process approach as a teachers’ approach in order to enhance student writing skills in recount text. The researcher used the literature review and some of the previous research which has been conducted before as the measurements toward the process approach could improve student writing skill in recount text whether they understood the material which given by the teacher or not. As a result of the literature review and previous research, the researcher found a significant influence of the process writing approach on writing progress and anxiety mainly in recount text. Based on this finding for written language research, the use of a process writing approach is recommended.